"Lymphocyte * Neutrophil" count decreased in SARS‐CoV‐2 Omicron patients in Shanghai with no significant change in CRP and SAA. Issue 10 (21st August 2022) - Chang, Huanhuan; Li, Jiao
Abstract: Background: At present, there is a new variant Omicron BA.2 of SARS‐CoV‐2. In some previous studies, it was found that CBC, NLR, CRP, SAA, etc. in patients with SARS‐CoV‐2 had a series of changes, which were significantly correlated with the diagnosis and prognosis of patients. Therefore, in order to find specific diagnostic indicators, we explore the changes in these blood indicators and inflammatory indicators in patients with the SARS‐CoV‐2 Omicron. Methods: A total of 127 Omicron confirmed patients who had visited fever clinic was selected as the positive group, and 75 Omicron excluded patients were selected as the negative group. We collected and analyzed the CBC, CRP, SAA test data, and clinical data of all subjects for analysis and statistics. Results: WBC, NEU, LYM, EOS, PLT, PCT, LYM * NEU count compared with the negative group were significantly lower ( p < 0.05); on the contrary, CNR were significantly higher ( p < 0.05); The levels of CRP and SAA were not significantly different from those of the negative group ( p > 0.05); the AUC of 0.781 for the diagnosis of LYM * NEU with an optimal cutoff value of 5.79, with a sensitivity and specificity of 68% and 73%, respectively, Youden index of 0.41, giving the best diagnostic performance. Conclusion: The decreased LYM * NEU count can be used as the early, rapid, and accurate diagnostic indicator for Omicron. While due to the attenuated toxicity of BA.2 sublineage, CRP and SAA had no significance in the differential diagnosis of confirmed patients. Abstract : SARS‐CoV‐2 Omicron mutant strain attacked Shanghai in late February 2022, CBC is the most widely used laboratory test for patients with symptoms suggestive of colds and is readily available even in primary hospitals. We selected 127 RT‐PCR positive patients admitted to the fever clinic of Shanghai TCM‐Integrated Hospital from March to May 2022 as the positive group, In addition, 75 patients in fever clinic with RT‐PCR negative in the same period were selected as the negative group. We collected and analyzed the CBC, CRP, SAA test data and clinical data of all subjects for analysis and statistics. WBC, NEU, LYM, EOS, PLT count, PCT level, LYM * NEU count in CBC compared with the negative group were significantly lower ( p < 0.05), on the contrary, CNR were significantly higher ( p < 0.05), LYM * NEU count giving the best diagnostic performance; The levels of CRP and SAA were not significantly different from those of the negative group ( p > 0.05). The decreased LYM * NEU count can be used as the early, rapid and accurate diagnostic indicator for Omicron. While due to the attenuated toxicity of BA.2 sublineage, CRP and SAA had no significance in the differential diagnosis of confirmed patients.